Exploring the molecular diversity and biomedicinal potential of marine invertebrates and South African actinomycetes for tuberculosis drug discovery - Acquah, Kojo Sekyi (Department of Chemistry, 2022)
Tuberculosis (TB) which is caused by Mycobacterium tuberculosis (Mtb), is the leading cause of death from a single infectious disease and remains a global health threat. Although there is medicine for treating TB, it still kills millions each year. This is due to a lengthy and demanding TB treatment regimen with associated problems of adverse drug-drug interactions and toxicities. Several resistant strains of Mtb, which are difficult and more expensive to treat, have also emerged. Therefore, there is a need to discover new potent and safe TB drugs to effectively treat Mtb with its resistant strains. Less explored and biodiversity-rich ecosystems such as the marine environment and South Africa (SA)'s fauna and flora have been a source of new bioactive natural products (NPs). A range of marine invertebrates and SA actinomycetes were therefore studied for the discovery of new antimycobacterial NPs. Several organic and aqueous marine invertebrate extracts were screened for their in vitro inhibitory activity against the Mtb strain H37Rv. The chemical components of two out of 54 active extracts were dereplicated using 1H NMR, HR-LCMS with GNPS molecular networking. The extracts were subsequently subjected to an activity-guided isolation process to yield heteronemin from Hyrtios reticulatus extract, and bengamides P and Q from Jaspis splendens extract. A new bengamide derivative was putatively identified in the molecular network of Jaspis splendens extract, and its structure predicted based on the similarity of its MS/MS fragmentation pattern to that of other bengamides. The isolated bioactive metabolites and semi-pure fractions exhibited antimycobacterial activity with MIC90 in the range of < 0.24 to 62.50 µg/mL. This is first report of antitubercular activity of bengamides P and Q. In studies on actinomycetes, the organic extract of a liquid culture of the South African Streptomyces strain Muiz4Y exhibited antimycobacterial activity against Mycobacterium aurum strain A+ and Mtb strain H37Rv. HR-LCMS analysis of the crude extract for dereplication suggested the presence of new compounds. A bioactivity, spectroscopy and spectrometry guided isolation procedure led to the isolation of three new natural products, a β-carboline alkaloid (1- (1,2-dihydroxyethyl)-1,2,3,4-tetrahydro-β-carboline-3-carboxylic acid), a peptide (N-(2- phenylacetyl)-serine), and a glycosylated lactone (4-O-(β-glucopyranosyl)-5-(hydroxymethyl)-3- (4-methylpentyl)-5,6-dihydro-2H-pyran-2-one), together with known compounds 3,6- bis(phenylmethyl)-2,5-piperazinedione and 2,4,6-triphenylhex-1-ene. The structures of the isolated compounds were elucidated based on spectroscopic methods including 1D and 2D NMR, MS, as well as by comparison with the relevant literature. Only 2,4,6-triphenylhex-1-ene exhibited antimycobacterial activity against Mtb strain H37Rv with an MIC90 of 5.8 µg/mL. The novel rare South African Actinomycete Kribbella speibonae strain SK5 exhibited antimycobacterial activity against Mycobacterium aurum A+. Dereplicating the crude extract of a large-scale culture of strain SK5 using 1H NMR, genome mining and HR-LCMS with GNPS molecular networking showed that it is a prolific producer of hydroxamate siderophores including new congeners. Two new analogues, dehydroxylated desferrioxamines, speibonoxamine and desoxy-desferrioxamine D1, were isolated, together with four known hydroxamates, desferrioxamine D1, desferrioxamine B, desoxy-nocardamine and nocardamine, and a diketopiperazine (DKP). The isolated compounds were characterized by the analysis of HRESIMS and 1D and 2D NMR data, as well as by comparison with the relevant literature. Three new dehydroxy desferrioxamine derivatives were tentatively identified in the molecular network of K. speibonae strain SK5 extracts, and structures were proposed based on their MS/MS fragmentation patterns. A plausible spb biosynthetic pathway was proposed. To the best of our knowledge, this is the first report of the isolation of desferrioxamines from the actinobacterial genus Kribbella. The isolated compounds were inactive against Mtb strain H37Rv and Mycobacterium aurum A+. This study confirmed the marine environment as a source of new antimycobacterial NPs and established South African actinomycete as a source of new bioactive NPs.